Bank leverage and monetary policy's risk-taking channel: evidence from the United States - Giovanni Dell'Ariccia; Luc Laeven; Gustavo A. Suarez (European Central Bank (ECB), 2016)
We present evidence of a risk-taking channel of monetary policy for the U.S. banking system. We use confidential data on banks' internal ratings on loans to businesses over the period 1997 to 2011 from the Federal Reserve's survey of terms of business lending. We find that ex-ante risk taking by banks (measured by the risk rating of new loans) is negatively associated with increases in short-term interest rates. This relationship is more pronounced in regions that are less in sync with the nationwide business cycle, and less pronounced for banks with relatively low capital or during periods of financial distress.
Keywords: E43; E52; G21; 330; banks; interest rates; leverage; monetary policy; risk